Histoquímica de la corteza de cinco angiospermas de una selva baja de Oaxaca - Paredes, Claudia; Quintanar, Alejandra; Acosta, Salvador; de la Paz Pérez, Carmen; Torre-Blanco, Alfonso (Instituto de Ecología, A.C., 2016)
Anatomical and histochemical features of the bark of Cercidium plurifoliolatum Micheli, Ipomea pauciflora Martens & Galeotti, Jatropha andrieuxii Muell. Arg., Lysiloma divaricata (Jacq.) MacBride, Ziziphus amole (Sessé & Mociño) M.C. Johnston from a seasonal dry forest of Oaxaca were analyzed. Transverse, tangential and radial sections were obtained from pieces of bark that included sapwood. The terminology of Trokenbrodt (1990) for anatomical characters was used. Lipids, pectins, calcium pectates, lignin and polyphenols were visualized by histochemical reactions. Two types of rays were observed: the first type form fanlike structures that become tangential bands; in the other type, rays are interrupted by small tangential structures such as axial parenchyma, fibers or groups of sclereids. It is noteworthy the radial array of axial parenchyma in Jatropha. Most cells of all species showed a strong reaction to calcium pectates. The composition of cellular contents shows a great diversity; noteworthy is the strong reaction to polyphenols, calcium pectates and oils in Jatropha’s secretory canals. It is evident a general pattern of lignification from the axial parenchyma outwards. The presence of abundant crystals was observed in the five species analyzed. Differences in the histchemical features of the bark between the species are discussed.